PENGARUH PEMBELAJARAN IPS MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PADA MATERI DINAMIKA INTERAKSI MANUSIA DENGAN LINGKUNGAN KELAS VII SEMESER GENAP SMP MUHAMMADIYAH 12 GRESIK - Widianto, Hari (Universitas Negeri Surabaya, 2018)
This is study aims to asses the effect of the use of Discovery Learning model for creative thinking abilities in teaching social studies on dynamics of? human interaction with the environment. Subject of this research is a class VII SMP Muhammadiyah 12 Gresik. Overing three classes used in this study, include VII G as a class test, VII E as the experimental group, and VII F as a control group. Lass tests are intended to test the instruments which will be used to retrieve data students? crative thinking abilities.??????????? This is a quantitative research approach based on the test scores of creative thinking abilities. The indicators of creative thinking abilities consist of fluent thinking, flexible thinking, original thinking, and elaborate thinking in which the scores or values are totaled and analyzed using t-test two independent samples. On the validity test, it is obtained that the r counting > r critical (0.334), namely item 1= 0.57 and item 2= 0.56 which are considered as valid and it can be used. In the test of reliability, the r counting >r critical (0.60), namely ? value 0,80 means greater than 0.60. Thus the entire items instrument is reliable. The result of hypothesis testing can be seen from the data that has been analyzed by t- counting 7,633> t-table 2,00 (?= 0,05). It can be concluded that the probability of error in this study still bellow 0.05. Hypothesis testing can be decided that with the high price of? 7,633 t-test has significance level of 0.000 turning out be the position which is stil far below the value of ?= 0,05.??????????? This study threfore managed to reject H0 at significance level of 5%. Furthermore, it can be concluded that the H1 was proved right. Mean in the pretest of the experimental group is 69 and Mean in the posttest of the experimental group is 83.1. While the mean pretest of the control group is 68 and the mean the posttest of the control group is 75.5. This is an evidence that the increasing scores of the experimental class happens after this class has been given the treatment with Discovery Learning model. Thus, we can conclude that the creative thinking abilities of students in the experimental group is higher than the control group. Indeed, Discovery Learning model has the positive effect on students? ability to thing creatively.?